Tropas extranjeras, tránsito de tropas y operaciones de mantenimiento de la paz (2021)
This article aims to clarify fundamental concepts such as troops, foreign troops and troops in transit, among other terms, as well as to explain some issues related to the mission of foreign troops in peacekeeping operations, since the arrival in the country of a United States Security Force Assistance Brigade (SFAB) to help Colombia in its fight against drug trafficking, has caused several controversies in the Senate, mainly because there is no clarity on the concepts just mentioned. It is considered that a legal distinction must be made of the concept of troops and, equivalently, a definition of foreign troops should be made.